MicroRNA profiling of the pubertal mouse mammary gland identifies miR-184 as a candidate breast tumour suppressor gene. Issue 1 (December 2015) - Phua, Yu; Nguyen, Akira; Roden, Daniel; Elsworth, Benjamin; Deng, Niantao; Nikolic, Iva; Yang, Jessica; Mcfarland, Andrea; Russell, Roslin; Kaplan, Warren; Cowley, Mark; Nair, Radhika; et al.
Abstract Introduction The study of mammalian development has offered many insights into the molecular aetiology of cancer. We previously used analysis of mammary morphogenesis to discover a critical role for GATA-3 in mammary developmental and carcinogenesis. In recent years an important role for microRNAs (miRNAs) in a myriad of cellular processes in development and in oncogenesis has emerged. Methods microRNA profiling was conducted on stromal and epithelial cellular subsets microdissected from the pubertal mouse mammary gland. miR-184 was reactivated by transient or stable overexpression in breast cancer cell lines and examined using a series ofin vitro (proliferation, tumour-sphere and protein synthesis) assays. Orthotopic xenografts of breast cancer cells were used to assess the effect of miR-184 on tumourigenesis as well as distant metastasis. Interactions between miR-184 and its putative targets were assessed by quantitative PCR, microarray, bioinformatics and 3′ untranslated region Luciferase reporter assay. The methylation status of primary patient samples was determined by MBD-Cap sequencing. Lastly, the clinical prognostic significance of miR-184 putative targets was assessed using publicly available datasets. Results A large number of microRNA were restricted in their expression to specific tissue subsets. MicroRNA-184 (miR-184) was exclusively expressed in epithelial cells and markedly upregulated during differentiation of the proliferative, invasive cells of the pubertal terminal end bud (TEB) into ductal epithelial cellsin vivo. miR-184 expression was silenced in mouse tumour models compared to non-transformed epithelium and in a majority of breast cancer cell line models. Ectopic reactivation of miR-184 inhibited the proliferation and self-renewal of triple negative breast cancer (TNBC) cell linesin vitro and delayed primary tumour formation and reduced metastatic burdenin vivo . Gene expression studies uncovered multi-factorial regulation of genes in the AKT/mTORC1 pathway by miR-184. In clinical breast cancer tissues, expression of miR-184 is lost in primary TNBCs while the miR-184 promoter is methylated in a subset of lymph node metastases from TNBC patients. Conclusions These studies elucidate a new layer of regulation in the PI3K/AKT/mTOR pathway with relevance to mammary development and tumour progression and identify miR-184 as a putative breast tumour suppressor.